2009
DOI: 10.1080/09593980802664711
|View full text |Cite
|
Sign up to set email alerts
|

Regression equations to predict 6-minute walk distance in middle-aged and elderly adults

Abstract: Six-minute walk distance (6MWD) is commonly used as a measure of functional exercise capacity in clinical practice and research. Regression equations to predict 6MWD in healthy individuals are available, but the equations predict distances that vary considerably for an individual. The aims of this study were to 1) measure 6MWDs in healthy Caucasian Australians aged 45-85 years; 2) determine whether evidence exists for Australian-specific prediction equations for Caucasian individuals by comparing measured 6MWD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 13 publications
3
81
4
Order By: Relevance
“…However, it should be borne in mind that physically fit individuals were excluded. Habitual physical activity has been evaluated in seven studies of 6MWT reference values, (10)(11)(12)(16)(17)(18)(19) basis of that finding, the 5th percentile for the 6MWD was calculated separately for values above and below the median. The lower limit, transformed into a proportion, was found to be 81% of the value predicted for both groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it should be borne in mind that physically fit individuals were excluded. Habitual physical activity has been evaluated in seven studies of 6MWT reference values, (10)(11)(12)(16)(17)(18)(19) basis of that finding, the 5th percentile for the 6MWD was calculated separately for values above and below the median. The lower limit, transformed into a proportion, was found to be 81% of the value predicted for both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Of the total of individuals under study, 104 (79%) were considered sedentary (total habitual physical activity questionnaire score < 8.0) and Stature was a relevant anthropometric variable for the prediction of the 6MWD in the present study, as it was in all such studies involving significant samples. (13)(14)(15)(16)(17)19) In the study conducted by Iwama et al, (18) only age and gender were taken into consideration when the regression equation was being derived. However, in the univariate analysis, the authors found that stature had the highest correlation coefficient, and its inclusion in the multivariate equation was therefore obligatory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiovascular data (such as heart rate and blood pressures) are predictors of 6MWD. 65,66 However, they cannot be advanced as an explanation, since the 2 groups have similar heart rate and blood pressure data and include similar percentages of smokers with chronotropic insufficiency.…”
Section: Evaluation Of Handicapmentioning
confidence: 99%